Comment : The danger of going online only. (1st July 2020) - Collins, Harry; Barnes, Bill; Sapienza, Riccardo
Abstract: Harry Collins, Bill Barnes and Riccardo Sapienza warn against a wholesale shift to virtual workshops and conferences following the COVID-19 pandemic